Structural and thermal retrofitting of masonry walls: An integrated cost-analysis approach for the Italian context. (15th May 2019) - Mistretta, Fausto; Stochino, Flavio; Sassu, Mauro
Abstract: Constructions ageing is a relevant problem in developed country like Italy. In particular, in case of existing masonry buildings, retrofitting interventions aimed at improving structural and thermal performances represents an obvious need. At the same time, sustainability awareness of buildings life-cycle has grown in the last years. Consequently, the whole life-cycle of constructions should be analyzed and assessed during the design of retrofitting interventions. In order to take into account these aspects new design and planning methods are necessary. This paper presents an integrated approach to evaluate structural and thermal retrofitting strategies for masonry walls. Economic and ecological costs of each examined retrofitting solution are compared, taking into account thermal and seismic capacity demand of the construction site. Given the economic cost, a set of retrofitting solutions for masonry panels have been mapped with a couple of parameters (structural strength Vs thermal insulation). An analogous mapping, considering the ecological cost due to equivalent CO2 production, have been performed. A methodology to find the best solution among a set of retrofitting solutions is presented, depending on the location of the building and its seismic and thermal characteristics. Examples, based on six retrofitting techniques located in four different sites in Italy, are analyzed to explain the effectiveness and the feasibility of the proposed method. The comparison between ecological and economical cost allowed to highlight the characteristics of the different interventions. Thermal performance proved to be more important in cold weather conditions while structural retrofitting is preferable in high seismic risk areas.